Like Water for Chocolate : A Novel in Monthly Installments With Recipes, Romances and Home Remedies - Esquivel, Laura, 1950-; Translated By Carol Christensen and Thomas Christensen (London Black Swan, 1993)
This novel is a romantic, poignant tale, touched with moments of magic, graphic earthiness and bittersweet wit. A sumptuous feast of a novel, it relates the bizarre history of the all-female De La Garza family.
Includes Illustrations.
Keywords: Mexico -- Families -- Magic